Stadt und Verstädterung im südpazifischen Raum - Buchholz, Hans Jürgen (ERDKUNDE, 1984)
Outside Hawaii towns and cities do not seem to be a characteristic criterion for the island countries of the South Pacific. But more than 35% of the entire population live in towns; that is above the average of the less developed countries of the world. It is astonishing, because the island countries are very small, most of their people still practise subsistence economy, and the low market-orientated economy belongs mainly to the agricultural sector. The under developed state of the division of labour is indicated by the low per centage of cash-earning persons, most of them employed by their governments. Additionally there exists no autochthonous urban tradition in the South Pacific; until today towns and cities correlate with the concentration of foreigners. In spite of the unfavourable conditions about 55 urban places are to be found in the whole area, sometimes pretty small, but always clearly differing from the rural settlements within their national context. The great number of urban places is based on the insular fragmentation and - resulting from this - on the difficult accessibility within the whole area. These factors are as important for the existence of so many political units (and each of them needs a capital) as for the rise and stability of the smaller secondary towns within the national frame.